2015
DOI: 10.3233/wor-131799
|View full text |Cite
|
Sign up to set email alerts
|

The effect of glare on eye movements when reading

Abstract: To my amazing son and daughter, with a patience beyond their years And To my dearest, always infinite being of love, light and endlessly supportive The first book on occupational health, "De Morbis Artificum Diatriba", included a chapter dedicated to "illness of people working with small objects".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
0
7
0
1
Order By: Relevance
“…The operators' visual system is under high strain [46] since the screens are flat. When glare is present or visibility is reduced, an increase of visual demands occurs [47], and the intensity of muscle blood flow in trapezius increases [48] leading to an increased risk of musculoskeletal disorders.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…The operators' visual system is under high strain [46] since the screens are flat. When glare is present or visibility is reduced, an increase of visual demands occurs [47], and the intensity of muscle blood flow in trapezius increases [48] leading to an increased risk of musculoskeletal disorders.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…High visual demands and increased load on intra-and extraocular muscles, such as stress on the accommodative-convergence system, are assumed to be involved in the development of eye symptoms (Bruenech and Kjellevold Haugen 2007;Sheedy et al 2003a;Zetterberg et al 2017). Regarding glare conditions, glare exposure have been reported to put extra load on the visual system by affecting accommodation (Shahnavaz and Hedman 1984;Wolska and Switula 1999), the binocular coordination (Glimne et al 2013), eye movements (Glimne et al 2015;Lin et al 2015), and the iris muscle's regulation of pupil size (Fry and King 1975;Hopkinson 1956). Therefore, intra and extraocular muscle strain may also be involved in the glare-induced eyestrain and discomfort observed here.…”
Section: Main Effects Of Visual and Psychological Stress Exposurementioning
confidence: 99%
“…In addition, glare exposure has been reported to result in increased orbicularis oculi muscle activity and decreased aperture size (eyelid squinting), decreased pupil size, increased trapezius blood flow, altered eye movements, decreased reading performance, and reduced productivity (Berman et al 1994;Glimne et al 2015;Glimne et al 2013;Gowrisankaran et al 2007;Hemphälä and Eklund 2012;Lin et al 2015;Mork et al 2016;Mork et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found that glare affects people with normal binocular vision and contributes to decreased productivity [18], increased blood flow in the trapezius muscle [19], and an increased blink rate [6]. There are several human adaptations or counteracting behaviors, including eyelid squinting, blinking, and changing postures, to reduce the negative effects of glare [6].…”
Section: Introductionmentioning
confidence: 99%